Local administration of vancomycin powder in orthopaedic fracture surgery: current practice and trends. Issue 1 (21st March 2023) - Marchand, Lucas S.; Sprague, Sheila; O'Hara, Nathan N.; Li, Chuan Silvia; O'Toole, Robert V.; Joshi, Manjari; Viskontas, Darius; Romeo, Nicholas; Hymes, Robert A.; Obremskey, William T.; Higgins, Thomas F.; Potter, Gorden D.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Objectives: Surgical site infections in orthopaedic trauma are a significant problem with meaningful patient and health care system–level consequences. Direct application of antibiotics to the surgical field has many potential benefits in reducing surgical site infections. However, to date, the data regarding the local administration of antibiotics have been mixed. This study reports on the variability of prophylactic vancomycin powder use in orthopaedic trauma cases across 28 centers. Methods: Intrawound topical antibiotic powder use was prospectively collected within three multicenter fracture fixation trials. Fracture location, Gustilo classification, recruiting center, and surgeon information were collected. Differences in practice patterns across recruiting center and injury characteristics were tested using chi-square statistic and logistic regression. Additional stratified analyses by recruiting center and individual surgeon were performed. Results: A total of 4941 fractures were treated, and vancomycin powder was used in 1547 patients (31%) overall. Local administration of vancomycin powder was more frequent in open fractures 38.8% (738/1901) compared with closed fractures 26.6% (809/3040) ( P < 0.001). However, the severity of the open fracture type did not affect the rate at which vancomycin powder was used ( P = 0.11). Vancomycin powder use varied substantially across the clinical sites ( P < 0.001). At the surgeon level, 75.0% used vancomycin powder in less than one-quarter of their cases. Conclusions: Prophylactic intrawound vancomycin powder remains controversial with varied support throughout the literature. This study demonstrates wide variability in its use across institutions, fracture types, and surgeons. This study highlights the opportunity for increased practice standardization for infection prophylaxis interventions. Level of Evidence: Prognostic—III.